Competence of Prospective Science Teachers in Reflecting on Science Teaching and Learning Activities - Nurlia Latipah; Nova Asvio; Muhammad Imaduddin (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2022)
Introduction/Main Objectives: This study aims to reveal the competence of prospective science teachers in reflecting on science teaching and learning activities at SMP/MTs. Background Problems: The ability to reflect on students' behaviour, providing an overview of the knowledge of prospective teachers to prepare a series of activities, methods or learning models that help students get a pleasant learning experience. Novelty: Observations and reflections use observation and reflection sheets which include the following components: (1) Activities carried out by students in gaining knowledge; (2) the efforts of students to understand the learning material; (3) the activities of students in communicating the results of their thoughts; and (4) reflective thinking skills of students. Research Methods: The type of survey research with the subject is 21 prospective science teachers who take internship course two at the Tadris IPA study program IAIN Bengkulu. The activity design provides opportunities for future teachers to observe and reflect on learning activities at several schools in Bengkulu City. Finding/Results: The results of this reflection are given a quality score and categorized under conditions of (1) Very Good; (2) Good; (3) Fairly Good; and (4) Not Good. The results showed that the competence of prospective science teachers in reflecting on students' learning activities in science subjects was in the excellent category. Conclusion: The ability of future science teachers who are very good at remembering students' learning activities has implications for the ability to prepare appropriate learning activities for students so that they can provide a fun learning for students.